2009
DOI: 10.1080/01494920903224277
|View full text |Cite
|
Sign up to set email alerts
|

Cutting the Wireless Cord: College Student Cell Phone Use and Attachment to Parents

Abstract: To better understand the dynamics of cell phone use among a sample of college students and their attachment for their parents, our study investigated the attitudes toward cell phone use, distinguishing patterns of cell phone users, and user group and gender differences related to attachment to parents among college students. Findings of this study point to implications for further research in three areas: cell phone use and adoption of special functions, family studies, and measurement improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…As children explore new freedom, parents try to assert control (Ling, 2000). Fathers, more so than mothers, tend to facilitate independence in their adolescent (Shulman & Seiffge-Krenke, 1997), which may be reflected in cell phone contact frequency in that fathers call and text children less than mothers do and children contact fathers less as well (Chen & Katz, 2009;Lee et al, 2009). Within families, Green (2007) argued that ''the cell phone is one area where parents and students must work to maintain an appropriate boundary' ' (p. 29).…”
Section: Rules Approach To Managing Connection and Autonomy In Emergimentioning
confidence: 99%
“…As children explore new freedom, parents try to assert control (Ling, 2000). Fathers, more so than mothers, tend to facilitate independence in their adolescent (Shulman & Seiffge-Krenke, 1997), which may be reflected in cell phone contact frequency in that fathers call and text children less than mothers do and children contact fathers less as well (Chen & Katz, 2009;Lee et al, 2009). Within families, Green (2007) argued that ''the cell phone is one area where parents and students must work to maintain an appropriate boundary' ' (p. 29).…”
Section: Rules Approach To Managing Connection and Autonomy In Emergimentioning
confidence: 99%
“…Due to the cellular phone’s physical and social dimensions, some have conceived it as an umbilical cord tying the child to their parents and encompassing the child’s space of independence (Ling, 2004). On the parents’ part, the potential for perpetual contact implied by the cell phone enables them to exercise “remote control” over their children as part of a normal, healthy separation process (Ribak, 2009), and it functions similarly when they go away to college (Lee, Meszaros, & Colvin, 2009). Young people, on the other hand, use their cell phones in order to amplify their experience of freedom and independence (see Ling, 2010).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Previous research showed that e-leisure might play an important role in the lives of families by influencing intimacy and communication between family members, as well as interaction between family members and society (Sharaievska, 2017). In some cases, family members were able to stay closer with each other by using cellphones when a child left for college (Lee, Mezaros, & Colvin, 2009), or by using Skype when relatives lived in a distant location (Horst, 2010;Ivan & Hebblethwaite, 2016). Bargh and McKenna (2004) discussed how couples in romantic relationships felt closer to each other due to their ability to text more often during the day, while Hertlein (2012) explained that couples felt closer because technology required them to express their feelings without relying on body language, as well as allowed time to phrase their concerns in a more constructive way.…”
Section: E-leisure and Familiesmentioning
confidence: 99%